Epoxy adhesive as well as preparation method and application thereof
By modifying lignin with anhydride esterification and crosslinking with epoxidized soybean oil, a three-dimensional network structure was constructed, which solved the problem of insufficient strength of epoxidized soybean oil adhesives and realized a high-performance, biodegradable epoxy adhesive suitable for bonding various materials and recyclable applications.
Patent Information
- Application Number
- CN202510942292.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-09
- Publication Date
- 2025-10-31
AI Technical Summary
How to prepare a bio-based high-strength adhesive using epoxidized soybean oil to meet structural bonding requirements and solve the problems of low recycling rate and environmental pollution caused by the irreversible cross-linking network of traditional epoxy resins.
Lignin is modified using anhydride-based esterification reagents. The esterification reaction reduces the polarity of lignin and introduces ester bonds. Combined with epoxidized soybean oil and organic carboxylic acids, a cross-linking reaction is carried out to construct a three-dimensional cross-linking network, forming a high-performance, biodegradable epoxy adhesive.
It has achieved the preparation of high-strength adhesives, improved the rigidity-flexibility balance and cross-linking density of adhesives, provided controllable degradation characteristics, is suitable for bonding a variety of materials, including metal-to-metal and non-metal cross-material bonding, and is recyclable.
Smart Images

Figure CN120865826A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive materials, and in particular to an epoxy adhesive, its preparation method, and its application. Background Technology
[0002] Epoxy resin, a key polymer material with an annual market size exceeding 90 billion yuan, faces a dual crisis due to its traditional system's high dependence on petroleum-derived monomers such as bisphenol A: on the one hand, the unsustainability of the raw material supply chain leads to its persistently high carbon footprint; on the other hand, the irreversible cross-linked network after curing results in a recycling rate of less than 5%, causing over 2 million tons of epoxy waste to be incinerated or landfilled annually, resulting in environmental pollution. Against this backdrop, constructing a fully bio-based epoxy resin system has become an inevitable choice for breaking the resource-environment dilemma.
[0003] Epoxidized soybean oil, as a typical bio-based epoxy resin raw material, is considered an important alternative to petroleum-based epoxy resins due to its renewable nature, low toxicity, and good epoxy group reactivity. However, the high flexibility of the epoxidized soybean oil molecular chain and the lack of rigid structural units result in a low crosslinking density after curing, leading to adhesives with significantly lower strength than traditional bisphenol A type epoxy resins, making it difficult to meet the requirements of structural bonding.
[0004] Therefore, it is of great significance to develop a bio-based high-strength adhesive using epoxidized soybean oil. Summary of the Invention
[0005] The main objective of this invention is to provide an epoxy adhesive, its preparation method, and its application. The technical problem to be solved is how to use epoxidized soybean oil to prepare a bio-based high-strength adhesive that meets the structural bonding requirements and is therefore more suitable for practical use.
[0006] The objective of this invention and the technical problem it solves are achieved by the following technical solution. A method for preparing an epoxy adhesive according to this invention includes the following steps:
[0007] Lignin is dissolved in an organic solvent, and an acid anhydride esterification reagent and catalyst are added to obtain an esterification system. An esterification reaction is carried out to obtain esterified modified lignin.
[0008] Epoxidized soybean oil, organic carboxylic acid and the aforementioned esterified modified lignin are mixed, and an epoxy accelerator is added to obtain a crosslinking system. A crosslinking reaction is carried out to obtain an epoxy adhesive.
[0009] In this study, by mass, the ratio of epoxidized soybean oil: organic carboxylic acid: the aforementioned esterified modified lignin was 1:0-0.6:0.2-1.5.
[0010] The objectives of this invention and the technical problems it addresses can be further achieved by the following technical measures.
[0011] Preferably, in the aforementioned method for preparing epoxy adhesives, the esterification agent is at least one selected from maleic anhydride, tung oil anhydride, and succinic anhydride; and / or,
[0012] The aforementioned organic carboxylic acids are at least one of malic acid, citric acid, and tannic acid.
[0013] Preferably, in the aforementioned method for preparing epoxy adhesive, the mass ratio of lignin to the aforementioned esterification reagent is in the range of 1:0.2 to 1.
[0014] Preferably, in the aforementioned method for preparing the epoxy adhesive, the catalyst is at least one selected from N,N-dimethylbenzylamine, 1-methylimidazolium, and 4-dimethylaminopyridine; and / or,
[0015] The mass of the aforementioned esterification system is 100%, and the mass of the aforementioned catalyst is 0.5% to 3%.
[0016] Preferably, in the aforementioned method for preparing epoxy adhesive, the esterification reaction is carried out at a temperature of 50–90°C for a time of 4–10 h.
[0017] Preferably, in the aforementioned method for preparing the epoxy adhesive, the epoxy accelerator is at least one selected from 2-ethyl-4-methylimidazolium, 2,4,6-tris(dimethylaminomethyl)phenol, and benzyldimethylamine; and / or,
[0018] The mass of the aforementioned crosslinking system is 100%, and the mass of the aforementioned epoxy accelerator is 0.5% to 1%.
[0019] Preferably, in the aforementioned method for preparing epoxy adhesive, the crosslinking reaction is carried out at a temperature of 60–90°C for a time of 0.5–3 h.
[0020] Preferably, in the aforementioned method for preparing the epoxy adhesive, the ratio of epoxidized soybean oil: organic carboxylic acid: the aforementioned esterified modified lignin is 1:0.2-0.6:0.2-1.5.
[0021] The objective of this invention and the solution to its technical problem are also achieved by the following technical solution. According to this invention, an epoxy adhesive is produced by crosslinking epoxidized soybean oil, organic carboxylic acid, and esterified modified lignin, wherein, by mass, the ratio of epoxidized soybean oil: organic carboxylic acid: the aforementioned esterified modified lignin is 1:0-0.6:0.2-1.5.
[0022] Anhydride groups were grafted onto the aforementioned esterified lignin.
[0023] The objective of this invention and the technical problem it solves are also achieved by the following technical solution. This invention proposes the application of the aforementioned epoxy adhesive in the field of adhesive materials.
[0024] By employing the above technical solution, the epoxy adhesive of the present invention, its preparation method, and its application have at least the following advantages:
[0025] The present invention proposes a method for preparing epoxy adhesives. This method involves introducing hydrophobic ester groups into the lignin structure via an anhydride-mediated esterification reaction to obtain esterified lignin. Then, epoxidized soybean oil and esterified lignin, or epoxidized soybean oil, organic carboxylic acids, and esterified lignin, are mixed and subjected to a cross-linking reaction to obtain the epoxy adhesive. This invention, through precise molecular structure control, simultaneously resolves the "compatibility-activity" contradiction of lignin, optimizes the rigidity-flexibility balance of epoxidized soybean oil, and introduces a dynamic cross-linking network, thereby preparing high-performance, biodegradable, and recyclable green adhesive materials.
[0026] Lignin, as the most abundant renewable aromatic polymer in nature, provides an ideal platform for developing high-performance bio-based epoxy resins due to its unique rigid phenylpropane structure and polyhydroxyl properties. However, the interfacial incompatibility between lignin's highly polar hydroxyl groups and the non-polar resin matrix, along with the low reactivity caused by strong intramolecular / intermolecular hydrogen bonding, results in a direct utilization rate of less than 2%. While conventional esterification modification can reduce lignin polarity, it sacrifices phenolic hydroxyl active sites, leading to insufficient crosslinking density. This "compatibility-activity" contradiction severely restricts the application of lignin in high-performance epoxy resins. This invention employs anhydride esterification modification of lignin, eliminating interfacial defects through covalent grafting. Specifically, during the lignin anhydride esterification modification process, anhydride esterification reagents preferentially react with the aliphatic hydroxyl groups on the lignin molecule to form ester bonds. This reaction introduces new ester groups onto the lignin molecule, increasing the molecular weight and reducing the molecular polarity. Furthermore, the carboxyl content in lignin increases. First, the anhydride groups undergo esterification with the lignin hydroxyl groups, releasing free carboxyl groups while forming ester bonds. Second, partial hydrolysis of the anhydride directly introduces additional carboxyl groups. Finally, unreacted anhydride molecules from the modification process also remain in the lignin structure as carboxyl groups. These three mechanisms work synergistically to increase the carboxyl content of lignin. This not only significantly reduces the polarity of lignin but also provides abundant active sites for subsequent covalent cross-linking with matrices such as epoxy resins.
[0027] The superior performance of the epoxy adhesive proposed in this invention stems from the three-dimensional cross-linked network synergistically constructed by epoxidized soybean oil and esterified lignin, or epoxidized soybean oil, organic carboxylic acid, and esterified lignin. In this system, the epoxy groups of epoxidized soybean oil undergo ring-opening reactions with the carboxyl groups of organic carboxylic acid, forming a hydroxyl-rich ester bond backbone that provides a flexible matrix for the material. Simultaneously, the rigid aromatic structure of esterified lignin restricts molecular chain movement, increases storage modulus, and significantly enhances cross-linking density. This unique "rigid-flexible" network structure design allows the adhesive to maintain excellent mechanical properties while also possessing controllable degradation characteristics, providing a new approach for developing high-performance bio-based epoxy resins.
[0028] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0029] Figure 1 These are the FTIR spectra of lignin before and after esterification modification in Example 1 of this invention;
[0030] Figure 2 This refers to the lignin esterification modification before and after in Example 1 of this invention. 31 P NMR spectrum;
[0031] Figure 3 This is a comparison of the molecular weight of lignin before and after esterification modification in Example 1 of the present invention;
[0032] Figure 4 This is a schematic diagram of the shear strength test method for epoxy adhesives in some embodiments of the present invention;
[0033] Figure 5 These are cyclic bonding performance demonstration diagrams of epoxy adhesives in some embodiments of the present invention. Detailed Implementation
[0034] To further illustrate the technical means and effects adopted by the present invention to achieve its intended purpose, the following, in conjunction with the accompanying drawings and preferred embodiments, provides a detailed description of the epoxy adhesive, its preparation method, application, structure, features, and effects according to the present invention. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable manner.
[0035] The present invention provides a method for preparing an epoxy adhesive, the steps of which include:
[0036] Lignin is dissolved in an organic solvent, and an acid anhydride esterification reagent and catalyst are added to obtain an esterification system. An esterification reaction is carried out to obtain esterified modified lignin.
[0037] Epoxidized soybean oil, organic carboxylic acid and the aforementioned esterified modified lignin are mixed, and an epoxy accelerator is added to obtain a crosslinking system. A crosslinking reaction is carried out to obtain an epoxy adhesive.
[0038] In this study, by mass, the ratio of epoxidized soybean oil: organic carboxylic acid: the aforementioned esterified modified lignin was 1:0-0.6:0.2-1.5.
[0039] Specifically, lignin is dissolved in an organic solvent. The organic solvent should be one that does not hydrolyze the esterification reagent but can dissolve lignin, such as acetone or N,N-dimethylformamide (DMF). Then, an anhydride-based esterification reagent and a catalyst are added to esterify the lignin. Preferably, the esterification reaction temperature is 50–90°C, and the time is 4–10 hours, yielding esterified modified lignin. First, the anhydride-based esterification reagent esterifies the hydroxyl groups of lignin to reduce its polarity. Second, the introduced carboxyl groups form covalent bonds with the epoxy groups of epoxidized soybean oil during the curing process, resulting in cross-linking. Finally, dynamic ester bonds are introduced after modification, allowing for cleavage under alkaline conditions, achieving effective recovery of the epoxy adhesive, thereby realizing substrate recovery and reducing waste. Preferably, the esterification reagent is at least one of maleic anhydride, tung oil anhydride, and succinic anhydride. Preferably, the mass ratio of lignin to the esterification reagent is in the range of 1:0.2–1. Preferably, the catalyst is at least one selected from N,N-dimethylbenzylamine, 1-methylimidazolium, and 4-dimethylaminopyridine. Preferably, the catalyst comprises 0.5% to 3% of the esterification system by mass.
[0040] Epoxidized soybean oil, organic carboxylic acid, and esterified lignin are mixed, and an epoxy accelerator is added to obtain a crosslinking system. A crosslinking reaction is then carried out. Preferably, the crosslinking reaction temperature is 60–90°C, and the time is 0.5–3 h, to obtain an epoxy adhesive. Preferably, the organic carboxylic acid is at least one of malic acid, citric acid, and tannic acid. Preferably, the epoxy accelerator is at least one of 2-ethyl-4-methylimidazolium, 2,4,6-tris(dimethylaminomethyl)phenol, and benzyldimethylamine. Preferably, the mass of the aforementioned crosslinking system is 100%, and the mass of the aforementioned epoxy accelerator is 0.5%–1%. The core of the superior performance of the epoxy adhesive proposed in this invention stems from the three-dimensional crosslinking network synergistically constructed by epoxidized soybean oil and esterified lignin, or epoxidized soybean oil, organic carboxylic acid, and esterified lignin. The reaction of epoxidized soybean oil, organic carboxylic acid, and esterified lignin is shown in formula (1). The epoxy groups of epoxidized soybean oil undergo ring-opening reactions with the carboxyl groups of organic carboxylic acids to form a hydroxyl-rich ester backbone, providing a flexible matrix for the material. At the same time, the rigid aromatic structure of esterified lignin restricts molecular chain movement, increases storage modulus, and significantly improves crosslinking density.
[0041] By weight, the ratio of epoxidized soybean oil: organic carboxylic acid: esterified lignin is 1:0-0.6:0.2-1.5. When the organic carboxylic acid content is too high, residual carboxyl groups induce plasticizing effects and increase hydrophilicity, weakening rigidity and water resistance, and potentially catalyzing epoxy group side reactions. For esterified lignin, too low a content will result in the loss of its aromatic ring structure's reinforcing effect, reducing modulus and dimensional stability; too high a content will lead to phase separation due to molecular aggregation, forming stress concentration points (reduced impact toughness), while excessive crosslinking will embrittle the material and worsen processing leveling properties. Preferably, the ratio of epoxidized soybean oil: organic carboxylic acid: the aforementioned esterified lignin is 1:0.2-0.6:0.2-1.5. Within this range, when the organic carboxylic acid provides sufficient carboxyl group crosslinking points, the epoxy adhesive exhibits higher mechanical strength.
[0042]
[0043] The present invention proposes an epoxy adhesive, wherein the aforementioned epoxy adhesive is produced by crosslinking epoxidized soybean oil, organic carboxylic acid and esterified modified lignin, wherein, by mass, the ratio of epoxidized soybean oil: organic carboxylic acid: the aforementioned esterified modified lignin is 1:0-0.6:0.2-1.5; and anhydride groups are grafted onto the aforementioned esterified modified lignin.
[0044] This invention proposes the application of the aforementioned epoxy adhesive in the field of adhesive materials. Due to its excellent adhesive properties, epoxy adhesives are suitable for bonding metals to metals, non-metals to non-metals, and metals to non-metals, such as cross-material bonding from aluminum to concrete. It can also be used in specialized engineering applications, such as in precision manufacturing fields like automotive brake pad bonding and aircraft cellular structure assembly.
[0045] The present invention will be further described below with reference to specific embodiments, but this should not be construed as a limitation on the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention still fall within the scope of protection of the present invention.
[0046] Unless otherwise specified, all materials and reagents mentioned below are commercially available products well known to those skilled in the art; unless otherwise specified, all methods described are methods known in the art. Unless otherwise defined, the technical or scientific terms used should have the ordinary meaning understood by those skilled in the art to which this invention pertains.
[0047] In the following examples and comparative examples, the tensile shear test method is as follows: Figure 1 As shown, the specific steps are as follows: Select stainless steel plate, aluminum plate, or wood plate as the substrate, and cut the substrate into strips with a width of 20mm, a length of 80mm, and a thickness of 5mm. Overlap two substrate pieces, apply epoxy adhesive to the overlapping area (20mm x 10mm), and use clips to fix the overlapping portion of the two substrate pieces. Then, allow it to fully cure at 160℃. Finally, conduct a tensile and shear test on the epoxy adhesive using a universal tensile testing machine.
[0048] Example 1
[0049] Lignin was dissolved in acetone, followed by the addition of maleic anhydride and N,N-dimethylbenzylamine to obtain an esterification system. The esterification system was reacted at 70°C for 6 hours to obtain esterified modified lignin. The mass ratio of lignin to acetone was lignin:acetone = 1:5. The mass ratio of lignin to maleic anhydride was lignin:maleic anhydride = 1:0.8. The mass of the esterification system was 100%, and the mass of N,N-dimethylbenzylamine was 1%.
[0050] By mass, epoxidized soybean oil, malic acid, and esterified lignin were mixed in a ratio of 1:0.2:0.5 until homogeneous. 2-Ethyl-4-methylimidazole was added as an epoxy accelerator to obtain a crosslinking system. The crosslinking system was reacted at 80°C for 1 hour to obtain a black, viscous liquid, which is the epoxy adhesive. The crosslinking system comprised 100% of the total mass, and 2-ethyl-4-methylimidazole comprised 1% of the total mass.
[0051] The substrate was selected as stainless steel sheet-to-stainless steel sheet, and a tensile-shear test was conducted, with a bond strength of 13.35 MPa.
[0052] Example 2
[0053] The difference between this embodiment and Embodiment 1 is that the ratio of epoxidized soybean oil: malic acid: esterified modified lignin is 1:0.4:0.7.
[0054] The substrate was selected as stainless steel sheet-to-stainless steel sheet, and a tensile-shear test was conducted, with a bond strength of 13.82 MPa.
[0055] Example 3
[0056] The difference between this embodiment and Embodiment 1 is that the ratio of epoxidized soybean oil: malic acid: esterified modified lignin is 1:0.4:1.
[0057] The substrate was selected as stainless steel sheet-to-stainless steel sheet, and a tensile-shear test was conducted, with a bond strength of 16.46 MPa.
[0058] Example 4
[0059] Lignin was dissolved in acetone, followed by the addition of tung oil anhydride and N,N-dimethylbenzylamine to obtain an esterification system. The esterification system was reacted at 70°C for 6 hours to obtain esterified modified lignin. The mass ratio of lignin to acetone was lignin:acetone = 1:5. The mass ratio of lignin to tung oil anhydride was lignin:maleic anhydride = 1:0.8. The mass of the esterification system was 100%, and the mass of N,N-dimethylbenzylamine was 1%.
[0060] By mass, epoxidized soybean oil, malic acid, and esterified lignin were mixed evenly in a ratio of 1:0.4:1.5. 2-Ethyl-4-methylimidazole was added as an epoxy accelerator to obtain a crosslinking system. The crosslinking system was reacted at 80°C for 1 hour to obtain a black, viscous liquid, which is the epoxy adhesive. The crosslinking system comprised 100% by mass, and 2-ethyl-4-methylimidazole comprised 1% by mass.
[0061] The substrate was selected as aluminum plate-aluminum plate, and a tensile-shear test was conducted, with a bond strength of 12.47 MPa.
[0062] Example 5
[0063] The difference between this embodiment and Embodiment 4 is that the ratio of epoxidized soybean oil: malic acid: esterified modified lignin is 1:0:1.
[0064] The substrate was selected as aluminum plate-aluminum plate, and a tensile-shear test was conducted, with a bond strength of 8.14 MPa.
[0065] Example 6
[0066] The difference between this embodiment and Embodiment 4 is that the ratio of epoxidized soybean oil: malic acid: esterified modified lignin is 1:0:1.5.
[0067] The substrate was selected as aluminum plate-aluminum plate, and a tensile-shear test was conducted, with a bond strength of 11.41 MPa.
[0068] Example 7
[0069] Lignin was dissolved in N,N-dimethylformamide, followed by the addition of succinic anhydride and 1-methylimidazole to obtain an esterification system. The esterification system was reacted at 50°C for 10 h to obtain esterified modified lignin. The mass ratio of lignin to N,N-dimethylformamide was lignin:N,N-dimethylformamide = 1:4. The mass ratio of lignin to succinic anhydride was lignin:succinic anhydride = 1:0.2. The mass of the esterification system was 100%, and the mass of 1-methylimidazole was 0.5%.
[0070] By mass, epoxidized soybean oil, citric acid, and esterified lignin were mixed evenly in a ratio of 1:0.4:0.7. Benzyl dimethylamine was added as an epoxy accelerator to obtain a crosslinking system. The crosslinking system was reacted at 90°C for 0.5 hours to obtain a black, viscous liquid mixture, which is the epoxy adhesive. The crosslinking system comprised 100% by mass, and benzyl dimethylamine comprised 0.5% by mass.
[0071] The substrate was selected as stainless steel sheet-to-stainless steel sheet, and a tensile-shear test was conducted, with a bond strength of 13.82 MPa.
[0072] Example 8
[0073] like Figure 5 As shown, the epoxy adhesive from Example 1 was applied to a small metal disc and bonded to a circular glass substrate. It was then fully cured at 160°C, resulting in a strong bond. The bonded area was moistened with 0.5–1 mol / L NaOH, with reapplication every 30 minutes to maintain moisture, until the adhesive layer peeled off (heating to 50–70°C can shorten the peeling time). After the metal disc completely detached from the glass substrate and no adhesive residue remained on the substrate surface, the alkaline hydrolysis-recovered resin aqueous solution was collected. This solution was placed in a dialysis bag with a molecular weight cutoff of 500 Da and dialyzed for 2 days. After dialyzing, the solution was freeze-dried to remove moisture, yielding desalted resin degradation products. Finally, the recovered products were dissolved in acetone for recoating and restoring bond strength. This environmentally friendly bonding / debonding mechanism significantly reduces maintenance costs and provides a sustainable solution for smart home systems, reusable electronics, and circular packaging design. This adhesive reconciles durability in extreme environments with eco-conscious recyclability, bridging the gap between high-performance industrial requirements and sustainable material innovation.
[0074] Comparative Example 1
[0075] By mass, epoxidized soybean oil, malic acid, and lignin were mixed evenly in a ratio of 1:0.4:1. 2-Ethyl-4-methylimidazole was added as an epoxy accelerator to obtain a crosslinking system. The crosslinking system was reacted at 80°C for 1 hour to obtain a black, viscous liquid mixture, which is the epoxy adhesive. The crosslinking system comprised 100% by mass, and 2-ethyl-4-methylimidazole comprised 1% by mass.
[0076] The substrate is selected as stainless steel sheet-to-stainless steel sheet, and a tensile and shear test is conducted, with a bond strength of 2.70 MPa.
[0077] Comparative Example 2
[0078] Lignin was dissolved in acetone, followed by the addition of acetyl chloride and N,N-dimethylbenzylamine to obtain an esterification system. The esterification system was reacted at 70°C for 6 hours to obtain esterified modified lignin. The mass ratio of lignin to acetone was lignin:acetone = 1:5. The mass ratio of lignin to acetyl chloride was lignin:acetyl chloride = 1:0.8. The mass of the esterification system was 100%, and the mass of N,N-dimethylbenzylamine was 1%.
[0079] By mass, epoxidized soybean oil, malic acid, and esterified lignin were mixed evenly in a ratio of 1:0.4:1. 2-Ethyl-4-methylimidazole was added as an epoxy accelerator to obtain a crosslinking system. The crosslinking system was reacted at 80°C for 1 hour to obtain a black, viscous liquid mixture, which is the epoxy adhesive. The crosslinking system comprised 100% by mass, and 2-ethyl-4-methylimidazole comprised 1% by mass.
[0080] The substrate was selected as stainless steel sheet-to-stainless steel sheet, and a tensile-shear test was conducted, with a bond strength of 4.43 MPa.
[0081] Test Experiment
[0082] 1. Fourier Transform Infrared Spectroscopy (FTIR) Measurement
[0083] The FTIR spectra of lignin before and after esterification modification in Example 1 were obtained, as follows: Figure 1 As shown. By Figure 1 It can be known that 3400cm -1 The weakening of the stretching vibration signals of both aromatic and aliphatic -OH groups in the vicinity indicates that the hydroxyl group successfully participated in the esterification reaction. And at 1740 cm⁻¹... -1 and 1760cm -1 There are obvious aliphatic ester bonds. In summary, the synergistic evidence of hydroxyl group consumption and ester bond formation fully confirms that hydrophobic ester groups were successfully introduced into the lignin structure through anhydride-mediated esterification, yielding the target product, esterified lignin.
[0084] 2. 31 P test
[0085] pass 31 Nuclear magnetic resonance (NMR) spectroscopy can accurately characterize the evolution of active hydroxyl groups in lignin, providing crucial evidence for verifying the effectiveness of esterification modification. The results are as follows: Figure 2As shown, esterification reduces the total hydroxyl content of lignin, especially the highly reactive aliphatic hydroxyl groups, indicating that acid anhydrides preferentially react with aliphatic hydroxyl groups to form ester bonds. Furthermore, the carboxyl content in lignin increases. This is because the esterification reaction between acid anhydride groups and lignin hydroxyl groups releases free carboxyl groups while forming ester bonds. Secondly, some acid anhydride hydrolysis directly introduces additional carboxyl groups. Finally, unreacted acid anhydride molecules during the modification process are also retained in the lignin structure as carboxyl groups. These three mechanisms work synergistically to generally increase the carboxyl content of lignin, which not only significantly improves the polarity and reactivity of lignin but also provides abundant active sites for subsequent covalent cross-linking with matrices such as epoxy resins.
[0086] 3. GPC Testing
[0087] Molecular weight analysis of lignin and esterified lignin was performed using gel permeation chromatography (GPC), such as... Figure 3 As shown, after esterification, both the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of lignin increased, indicating that the hydroxyl groups on the lignin molecules react with esterification reagents such as acid anhydrides. This reaction introduces new ester groups onto the lignin molecules. These new chemical groups increase the polarity and molecular weight of the molecules.
[0088] The technical features in the claims and / or specification of this invention can be combined, and the combination is not limited to the combinations obtained through reference in the claims. Technical solutions obtained by combining the technical features in the claims and / or specification are also within the scope of protection of this invention.
[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an epoxy adhesive, characterized in that, The steps include: Lignin is dissolved in an organic solvent, and an acid anhydride esterification reagent and catalyst are added to obtain an esterification system. An esterification reaction is carried out to obtain esterified modified lignin. Epoxidized soybean oil, organic carboxylic acid and the esterified modified lignin are mixed, and an epoxy accelerator is added to obtain a crosslinking system. A crosslinking reaction is carried out to obtain an epoxy adhesive. In this composition, by mass, the ratio of epoxidized soybean oil: organic carboxylic acid: the esterified modified lignin is 1:0-0.6:0.2-1.
5.
2. The preparation method according to claim 1, characterized in that, The esterification agent is at least one selected from maleic anhydride, tung oil anhydride, and succinic anhydride; and / or... The organic carboxylic acid is at least one of malic acid, citric acid, and tannic acid.
3. The preparation method according to claim 1, characterized in that, The mass ratio of lignin to the esterification reagent is in the range of 1:0.2 to 1.
4. The preparation method according to claim 1, characterized in that, The catalyst is at least one selected from N,N-dimethylbenzylamine, 1-methylimidazole, and 4-dimethylaminopyridine; and / or, The mass of the esterification system is 100%, and the mass of the catalyst is 0.5% to 3%.
5. The preparation method according to claim 1, characterized in that, The esterification reaction is carried out at a temperature of 50–90°C for 4–10 hours.
6. The preparation method according to claim 1, characterized in that, The epoxy accelerator is at least one selected from 2-ethyl-4-methylimidazolium, 2,4,6-tris(dimethylaminomethyl)phenol, and benzyldimethylamine; and / or, The crosslinking system comprises 100% by mass, and the epoxy accelerator comprises 0.5% to 1% by mass.
7. The preparation method according to claim 1, characterized in that, The cross-linking reaction is carried out at a temperature of 60–90°C for a time of 0.5–3 hours.
8. The preparation method according to claim 1, characterized in that, Epoxidized soybean oil: organic carboxylic acid: the esterified modified lignin = 1: 0.2-0.6: 0.2-1.
5.
9. An epoxy adhesive, characterized in that, The epoxy adhesive is produced by crosslinking epoxidized soybean oil, organic carboxylic acid, and esterified modified lignin, with the following mass ratio: epoxidized soybean oil: organic carboxylic acid: esterified modified lignin = 1:0-0.6:0.2-1.5; Anhydride groups are grafted onto the esterified lignin.
10. The application of the epoxy adhesive of claim 9 in the field of adhesive materials.